A comprehensive renewable energy program for Saudi Vision 2030. Issue 5 (September 2016) - Jurgenson, Stephen; Bayyari, Fadil M.; Parker, Jason
Abstract : Partner Stephen Jurgenson, Of Counsel Jason Parker and associate Fadil M. Bayyari from the Dubai office of international law firm Winston & Strawn explore lessons from South Africa's REIPP Program.